2022
DOI: 10.9734/ijecc/2022/v12i1131118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mulched and without Mulched Intercrops on Growth Yield and Fruit Quality of Kinnow Mandarin Plantation under Semi-Arid Irrigated Conditions

Abstract: The aim of the present was to analyze the effect of different intercrops with and without mulch on growth, yield and quality of kinnow mandarin orchard. The data of kinnow plant such as height, stem girth, canopy spread, and canopy volume were collected in the month of February 2020 before transplanting the intercrops. The intercrops under mulch and without mulch treatments have significant effect on growth of kinnow plant, the percent increase in plant height (3.22%) in kinnow + watermelon, stem girth (4.20%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Also, in the three-season table (3) all treatments the increase was significant in the fruit size, which was on the same line with the increase in the weight of the fruit compared to the control. This is in agreement with results of Kumar et al (2022), the aim of the effect of different intercrops on the average fruit weight were significantly affected by mulch and without mulch treatment. Also, among different intercropping systems tried, mango + guava +cowpea exhibited better performance which has been reflected in the form of panicle production, fruit weight and fruit yield.…”
Section: Characteristics Of Natural Fruiting Qualitysupporting
confidence: 93%
See 4 more Smart Citations
“…Also, in the three-season table (3) all treatments the increase was significant in the fruit size, which was on the same line with the increase in the weight of the fruit compared to the control. This is in agreement with results of Kumar et al (2022), the aim of the effect of different intercrops on the average fruit weight were significantly affected by mulch and without mulch treatment. Also, among different intercropping systems tried, mango + guava +cowpea exhibited better performance which has been reflected in the form of panicle production, fruit weight and fruit yield.…”
Section: Characteristics Of Natural Fruiting Qualitysupporting
confidence: 93%
“…Also, Salama et al (2019) pointed out that fruit yield and quality attributes of squash significantly improved than control treatment. These results are in line with those obtained by Kumar et al (2022) found that the number of fruits per tree, yield were significantly affected by mulch and without mulch treatments. Intercropped peas increased yield with maximum number of fruits (920), fruits weight (161.11g) and yield.…”
Section: Effect Of the Intercropping Total Yield Of Kg/tree (Fruits W...supporting
confidence: 93%
See 3 more Smart Citations